Impact of patient provider support agency on private sector engagement in Tuberculosis care in Eastern India - Narain, Smiti; Sagar, Vidya; Thankamma, Anupama; Mitra, Anindya (International Journal Of Community Medicine And Public Health, 2023)
Background: India is the country with the world’s largest burden of tuberculosis, with a large proportion of patients seeking care from the private healthcare sector, which is fragmented and unregulated. There are significant gaps across the patient care cascade in the private sector on account of underreporting, diagnostic delays, irrational and non-standardized regimens, and catastrophic health expenditures to patients. Considering the gaps, Jharkhand state of India had implemented patient provider support agency scheme under National TB elimination programme to improve private sector engagement, operational since 27 September 2019. PPSA is giving end-to-end NTEP TB service packages to patients seeking care in the private sector. Methods: This is a retrospective cross-sectional descriptive study using secondary data attained from the Nikshay web portal for Jharkhand and analyzed using Excel. Results: After the introduction of PPSA, the proportion of private sector notifications in Jharkhand increased from 22.9 percent in 2019 to 33.5 percent in 2020. The Private sector notification rate in the state showed an increase from 34 per lakh population to 39 per lakh population. Conclusions: Private sector engagement through PPSA has improved TB notification in Jharkhand. PPSA could sustain the provision of TB care in the private sector even during the COVID-19 pandemic. The access to quality data on patients seeking TB care in the private sector in the Nikshay web portal has improved since the implementation of the scheme resulting in better patient support and program monitoring.